Clinical Perspective of FDA Approved Drugs With P-Glycoprotein Inhibition Activities for Potential Cancer Therapeutics - Lai, Jiun-I; Tseng, Yu-Jhen; Chen, Ming-Huang; Huang, Chi-Ying F.; Chang, Peter Mu-Hsin (Frontiers in Oncology, 2020)
P-glycoprotein (also known as multidrug resistance protein 1 (MDR1) or ATP-binding cassette sub-family B member 1 (ABCB1) plays a crucial role in determining response against medications, including cancer therapeutics. It is now well established that p-glycoprotein acts as an ATP dependent pump that pumps out small molecules from cells. Ample evidence exist that show p-glycoprotein expression levels correlate with drug efficacy, which suggests the rationale for developing p-glycoprotein inhibitors for treatment against cancer. Preclinical and clinical studies have investigated this possibility, but mostly were limited by substantial toxicities. Repurposing FDA-approved drugs that have p-glycoprotein inhibition activities is therefore a potential alternative approach. In this review, we searched the Drugbank Database (https://www.drugbank.ca/drugs) and identified 98 FDA-approved small molecules that possess p-glycoprotein inhibition properties. Focusing on the small molecules approved with indications against non-cancer diseases, we query the scientific literature for studies that specifically investigate these therapeutics as cancer treatment. In light of this analysis, potential development opportunities will then be thoroughly investigated for future efforts in repositioning of non-cancer p-glycoprotein inhibitors in single use or in combination therapy for clinical oncology treatment.